INTELLECTUAL CAPITAL THROUGH CORPORATE VALUES WITH PROFITABILITY AS MEDIATION VARIABLE - Minda Utami, Eristy; Susanti, Neneng; R , Achmad Drajat S (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the influence of Intellectual Capital on company value with profitability as a mediating variable. The data used in this study is secondary data with a sampling method that is purposive sampling method. The populations in this study were companies that were registered in LQ 45 for the period of 2012-2016, which were than selected as 19 samples in this study. The analysis tool for testing hypotheses is path analysis. The results of this study are the effect of intellectual capital on company value on LQ 45 Index companies listed on the Indonesia Stock Exchange (IDX) in the period 2011-2016 through profitability as an mediating variable of 16,9%.